Pengembangan Media Flipscrap Book pada Materi Puisi SMA - Siti Shofa Nurhidayah16; D. Nurfajrin Ningsih; Aprilla Adawiyah (Universitas Suryakanca, 2026)
This article describes the development of Flipscrap Book learning media for poetry material in grade X of high school. The research method used is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model development research. The research subjects consisted of 3 material experts, 3 media experts, and 31 students in grade X-8. Data were collected through interviews, expert validation, and questionnaires. The results of the study concluded that the development of digital-based Flipscrap Book media was very feasible with a score of 92.77% (material expert validation), a score of 94.57% (media expert validation) with a very feasible category. The results of the student response questionnaire were very effective with an average score of 95.42%. Abstrak Artikel ini mendeskripsikan pengembangan media pembelajaran Flipscrap Book materi puisi di kelas X SMA. Metode penelitian yang digunakan adalah penelitian pengembangan model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Subjek peneliti terdiri dari 3 ahli materi, 3 ahli media, dan 31 peserta didik kelas X-8. Data dikumpulkan dengan wawancara, validasi ahli, dan angket. Hasil penelitian menyimpulkan bahwa pengembangan media Flipscrap Book berbasis digital sangat layak dengan memperoleh skor 92,77% (validasi ahli materi), skor 94,57% (validasi ahli media) dengan katerogi sangat layak. Hasil angket respon peserta didik sangat efektif dengan skor rata-rata 95,42%.